A cost of reproduction in male Atlantic cod (Gadus morhua) - Skjaeraasen, J E; Meager, J J; Hutchings, J A (Canadian Journal of Zoology, 2010)
In many species, females are thought to base their choice of mate on quality, which males signal through displays and body ornamentation. One important question is whether these signals represent an honest reflection of quality so that they carry an intrinsic cost to the male. A considerable body of evidence has revealed complex mating behaviours in gadoid fish, such as Atlantic cod (Gadus morhua L., 1758), for which male reproductive success may be related to some form of female choice. However, if present, the cost of male signalling is not clear. To test the hypothesis that male behavioural displays are energetically costly, we quantified the number of displays initiated by males during spawning, and their corresponding mass loss, in two separate experiments. The number of displays was positively associated with mass loss in both experiments, suggesting that reproductive displays are costly to males; they also may be regarded as an honest signal of quality upon which females could base their choice of mate. To our knowledge, this is the first study to demonstrate a cost of male reproductive behaviour in a broadcast-spawning fish.